Assessment of tumourigenic potential in long-term cryopreserved human adipose-derived stem cells - Yong, K.W.; Wan Kamarul Zaman, Wan Safwani; Xu, F.; Zhang, X.; Choi, J.R.; Wan Abas, Wan Abu Bakar; Omar, Siti Zawiah; Noor Azmi, Mat Adenan; Chua, K.H.; Pingguan-Murphy, Belinda (Wiley, 2016)
Cryopreservation represents an efficient way to preserve human mesenchymal stem cells (hMSCs) at early culture/passage, and allows pooling of cells to achieve sufficient cells required for off-the-shelf use in clinical applications, e.g. cell-based therapies and regenerative medicine. To fully apply cryopreserved hMSCs in a clinical setting, it is necessary to evaluate their biosafety, e.g. chromosomal abnormality and tumourigenic potential. To date, many studies have demonstrated that cryopreserved hMSCs display no chromosomal abnormalities. However, the tumourigenic potential of cryopreserved hMSCs has not yet been evaluated. In the present study, we cryopreserved human adipose-derived mesenchymal stem cells (hASCs) for 3 months, using a slow freezing method with various cryoprotective agents (CPAs), followed by assessment of the tumourigenic potential of the cryopreserved hASCs after thawing and subculture. We found that long-term cryopreserved hASCs maintained normal levels of the tumour suppressor markers p53, p21, p16 and pRb, hTERT, telomerase activity and telomere length. Further, we did not observe significant DNA damage or signs of p53 mutation in cryopreserved hASCs. Our findings suggest that long-term cryopreserved hASCs are at low risk of tumourigenesis. These findings aid in establishing the biosafety profile of cryopreserved hASCs, and thus establishing low hazardous risk perception with the use of long-term cryopreserved hASCs for future clinical applications.